INVESTIGATION OF PRE-SERVICE MATHEMATICS TEACHERS' CREATIVE THINKING TENDENCIES - Erdoğan, Fatma; Yıldız, Feyza (My University, 2021)
Creative thinking has played a critical role in a number of fields such as science, technology, economy, and education. Given the necessity of creative thinking in mathematics teaching, it can be argued that teachers are responsible for transforming their students into creative thinkers. In this context, the present study aims to determine pre-service mathematics teachers’ levels of critical thinking tendency and the main as well as interaction effects of demographic variables (i.e., gender, year, and academic achievement) on critical thinking tendency. The study makes use of the survey and causal-comparative designs. The study included 130 pre-service elementary mathematics teachers and used “The Marmara Creative Thinking Tendencies Scale” developed by Özgenel and Çetin (2017) as the data collection tool. Descriptive and two-way analysis of variance were used. The study reported high creative tendency levels of pre-service teacher. Another outcome of the study shows that the variables of gender, year, and academic achievement did not have significant main effect on creative tendency levels of pre-service teachers. Besides, the interaction effect of gender-year and gender-academic achievement on the creative thinking tendency levels of pre-service teachers are not statistically significant. Based on the findings, recommendations for future research and educational implications are presented.
Keywords: Eğitim; Eğitim Araştırmaları; Matematik